Upaya Bimbingan Orang Tua Dalam Membentuk Akhlak Anak - Suhada Suhada; Ibnu Nur Muhamad Akbar; H. Alwi (UNIVERSITAS RAHARJA, 2020)
This study examines the role of parents in shaping children's morals at the Ibnu Syuhada Education Foundation. Moral education which is only limited to the concept of theoretical discussion in the literature, very interesting to study. The aim is to critically analyze how to encourage parents in compiling children's character at the Ibnu Syuhada Education Foundation in the City of Tangerang. As a result it is expected to be able to use consideration for parents or foundations in forming the morals of al-karimah in educational institutions.This research is a qualitative study,which makes the Ibnu Syuhada Education Foundation Tangerang City as a research site. The method used in this study is the method of observation, interviews, and observation. Then the data are analyzed in a complete way using the Miles and Hubermen model, namely data collection, data reduction, data display, then drawing conclusions / verification (drawing conclusions. The results showed: (1) the application of moral education in Yaspi Ibnu Syuhada was in accordance with the objectives of education. Based on observations during the research in the learning process with the intention of the teacher and students have implemented it. (2) provide education in accordance with the curriculum that has been applied at the Ibnu Syuhada Education Foundation and ask students at the specified time (3) provide role models in worship and exemplary morals in al-karimah and provide protection for children to practice their knowledge obtained from madrasa while at home.